Analisis Penggunaan Uang Elektronik dalam Mendorong Pengembangan Sektor Industri UMKM di Era Industri 5.0 - Nabillah, Sri Rahayu Afanin; Ayuningtyas, Fitri Juniwati (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
As time goes by, the development of technology and the internet is increasingly rapid in the midst of the Industry 5.0 era, accompanied by the digitalization of banking, which has a positive impact on industry players, but negative impacts also appear to be felt by MSME players. The change in system and culture requires them to re-adapt to these conditions. This research aims to analyze the relationship between the amount of electronic money in circulation, the number of fintech players, and the number of peer-to-peer lending bank accounts and their influence on MSME financing in Indonesia in the industrial era 5.0. This research adopts a quantitative approach, analyzing secondary time series data from January 2018 to August 2023. This study reveals a positive and significant impact of both electronic money circulation and peer-to-peer lending accounts on MSME financing. This suggests that higher levels of e-money and peer-to-peer lending accounts potentially promote MSME growth in industry 5.0. However, the number of fintech players did not exhibit a significant influence, indicating its lack of association with MSME development in this context.